Stroke patients perceptions of upper limb use in ADL after rehabilitation using a virtual reality (VR) intervention - Richardson, Andrew (2017)
Virtual Reality interventions are increasingly being researched with regard to their role in upper limb rehabilitation following stroke. Despite emerging evidence to demonstrate their efficacy in increasing motor function, there is weaker evidence to demonstrate an effect on performance in daily living activities. The Motor Activity Log (MAL) was used as a secondary outcome measure in the Wii Stroke Therapy for Arm Rehabilitation (Wii STAR) feasibility Randomised Controlled Trial, to explore whether there is any change in patients’ perceptions of how well, and how often they used their paretic upper limb during daily living activities (ADL) .